2018
DOI: 10.1039/c7nj04969b
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological profile of mixed opioid agonist/N-VGCC blocker peptides

Abstract: Novel mixed opioid agonist/N-VGCC blocker peptides, design, synthesis and biological profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The synthesis of the novel free C -terminal peptides 1, 2, and 3 was performed by solid-phase peptide synthesis (SPPS) [31,32,33] on Cl-Trt chloride resin (0.1 mmol scales; loading: 1.6 mmol Cl-/g). All amino acids have the Fmoc- N -terminus and the following side-chain protecting groups: tert -butyloxy-carbonyl (Boc) for Lysine and Tryptophan, 2,2,4,6,7-Pentamethyldihydrobenzofuran-5-sulfonyl (Pbf) for Arginine, O- tert -butyl (O t Bu) for Tyrosine, trityl (Trt) for Cysteine.…”
Section: Chemistrymentioning
confidence: 99%
“…The synthesis of the novel free C -terminal peptides 1, 2, and 3 was performed by solid-phase peptide synthesis (SPPS) [31,32,33] on Cl-Trt chloride resin (0.1 mmol scales; loading: 1.6 mmol Cl-/g). All amino acids have the Fmoc- N -terminus and the following side-chain protecting groups: tert -butyloxy-carbonyl (Boc) for Lysine and Tryptophan, 2,2,4,6,7-Pentamethyldihydrobenzofuran-5-sulfonyl (Pbf) for Arginine, O- tert -butyl (O t Bu) for Tyrosine, trityl (Trt) for Cysteine.…”
Section: Chemistrymentioning
confidence: 99%
“…Of note, Stefanucci et al have developed mixed opioid agonist/N-VGCC blocker peptides for the treatment of pain. Furthermore, MORs and N-VGCCs are co-localized on pain-modulating neurons in the central nervous system (CNS) [11]. The development of a multi-target molecule combining an opioid pharmacore and an N-VACC blocker may provide synergistic activity and could serve as a therapeutic candidate for the treatment of severe chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Nowadays, with the deep study of AMPs, rational modification of natural AMPs and de novo designed AMPs have become an important approach for improving the antimicrobial properties of AMPs, 18 including site-directed amino acid substitutions, 19 amino acid end-tagging, 20 and design of linear pseudo-peptides. 21 However, although numerous studies about AMPs as food preservatives have been reported, they still have some drawbacks, including high synthetic cost, poor antimicrobial activity, and a narrow antimicrobial spectrum, which limit their practical applications. [1][2][3][4]22 Therefore, regarding the development of food preservatives, the design of ultra-short AMPs with potent broad-spectrum antimicrobial effects would contribute to further advancing the development of peptide-based food preservatives based on the inherent advantages of AMPs with favorable biodegradability.…”
Section: Introductionmentioning
confidence: 99%